Dynamic frequency reuse: a method for interference mitigation in OFDMA Based LTE-A Networks - Reza, Asif; Abdullah, Khaizuran; Ismail, Ahmad Fadzil; Raisa, Farah; Mohd Ramli, Huda Adibah; Hashim, Wahidah (School of Engineering, Taylor's University, 2017)
Spectrum scarcity is one of the most discussed restraining aspects in wireless communication system. To solve this issue Frequency Reuse (FR) concept is introduced. It is a promising development to fulfil the requirement of Long Term Evolution Advanced (LET-A). With the introduction of FR comes the problem of Inter Cell Interference as the neighboring eNodeBs (eNB) which uses the same frequency band that will act as an interference source. In this paper, a Dynamic Frequency Reuse (DFR) method is anticipated. Continuous optimization of resource allocation of each cell is considered in this method. The important focus of the paper is to expand the capacity of the users placed in cell edge areas by reducing out of cell interference. Simulation has been done to prove that the proposed scheme leads to efficient resource management.